An in vitro study on disinfection of titanium surfaces. Issue 10 (10th February 2016) - Widodo, Arifo; Spratt, David; Sousa, Vanessa; Petrie, Aviva; Donos, Nikolaos
Abstract: Objective: The aim of this in vitro study was to evaluate the efficacy of different methods used for the decontamination of titanium surfaces previously infected with a Staphylococcus aureus biofilm. Materials and Methods: S. aureus biofilms were grown on three different titanium surfaces ( n = 114); polished, sandblasted large‐grit acid‐etched (SLA) and SLActive. The experimental groups were divided into six different disinfection modalities as follows: (i) rinsing with phosphate‐buffered saline, (ii) rinsing with chlorhexidine digluconate 0.2% (CHX), (iii) application of photodynamic therapy (PDT), (iv) use of cotton pellet, (v) use of titanium brush (TiB) and (vi) the use of TiB and PDT. The decontamination effect of each modality was evaluated by microbial culture analysis and by scanning electron microscopy imaging. Two‐way analysis of variance (ANOVA) and Bonferroni's post hoc comparisons were used to compare mean differences between colony‐forming units per millilitre (CFU/ml) values, surfaces and treatments ( P < 0.025). Results: This study demonstrated that the combination protocol (TiB and PDT) was the most effective in reducing S. aureus ( P < 0.025) on polished (2.0 × 10 3 CFU/Disc) and SLA surface (6.9 × 10 3 CFU/Disc). On the SLActive surface, the combination treatment was not significantly different to the TiB group (1.0 × 10 5 CFU/Disc) or the PDT group (2.0 × 10 5 CFU/Disc). Conclusion: The combined technique of TiB and PDT was shown to be an efficient method in reducing the number of S. aureus in both polished and rough titanium surfaces. These findings prompt further investigations in titanium decontamination techniques with a combination of TiB and PDT within a natural microcosm bacterial environment.